Il rifiuto delle vaccinazioni obbligatorie per motivi di coscienza. Spunti di comparazione (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Le “nuove” obiezioni di coscienza nelle società multiculturali. Il rifiuto dell’obbligo vaccinale - 2. Religioni e vaccini - 3. La situazione negli altri Paesi, in particolare il caso degli USA - 4. L’obbligo vaccinale in Italia - 5. È configurabile il diritto all’obiezione di coscienza rispetto alle vaccinazioni obbligatorie?The Refusal of Mandatory Vaccinations for Conscientious Reasons. A Comparative OverlookABSTRACT: The paper analyzes the possibility to design a new shape of conscientious objection : the refusal of mandatory vaccinations due to religious or ideological reasons. Some religions are against vaccines because of the ingredients they contain. In other cases the refusal to be vaccinated is based on the idea that only God can protect health. The legislatures of some Countries recognize the conscientious objection to mandatory vaccinations. The paper focuses the topic in a comparative perspective, paying attention to the italian and european context.